2010
DOI: 10.1002/chem.200900764
|View full text |Cite
|
Sign up to set email alerts
|

The Protonation of HSO3F: Preparation and Characterization of Fluorodihydroxyoxosulfonium Hexafluoroantimonate [H2SO3F]+[SbF6]

Abstract: Sulfurtrioxide reacts with the superacidic solutions XF/SbF(5) (X=H, D) to form the corresponding salts [X(2)SO(3)F](+)[SbF(6)](-), which are the protonated forms of fluorosulfuric acid. The salts have been characterized by vibrational spectroscopy and a single-crystal structure analysis. [H(2)SO(3)F](+)[SbF(6)](-) crystallizes in the monoclinic space group P2(1)/n (no. 14) with four formula units in the unit cell. The crystal structure possesses a distorted tetrahedral O(3)SF skeleton of the cations, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…HF molecules were added to the calculated gas phase structure to simulate the hydrogen bridges, which have a significant influence on the O–H and N–H vibrations. In several previously reported studies we found that this simple modeling of the solid state leads to frequencies that are much closer to the experimental ones than calculations of the free cations 20,21. The infrared spectra of H 3 CC(OH)NH 2 + MF 6 – (M = As ( 1 ), Sb ( 3 )) display a ν (OH) band (3625 cm –1 ( 1 ), 3601 cm –1 ( 3 )) above the very intensive and broad bands of ν (NH 2 ).…”
Section: Resultssupporting
confidence: 75%
“…HF molecules were added to the calculated gas phase structure to simulate the hydrogen bridges, which have a significant influence on the O–H and N–H vibrations. In several previously reported studies we found that this simple modeling of the solid state leads to frequencies that are much closer to the experimental ones than calculations of the free cations 20,21. The infrared spectra of H 3 CC(OH)NH 2 + MF 6 – (M = As ( 1 ), Sb ( 3 )) display a ν (OH) band (3625 cm –1 ( 1 ), 3601 cm –1 ( 3 )) above the very intensive and broad bands of ν (NH 2 ).…”
Section: Resultssupporting
confidence: 75%
“…[8] The S=O stretching vibration is observed at nearly constant wavenumbers around 1400 cm -1 , which is comparable to that observed for the H 3 SO 4 + and H 2 SO 3 F + cations. [8,9] This is expected due to the similarity of the cations and the absence of interionic interactions. The two S-O stretching vibrations at 1073 and 956 cm -1 are better described as modes between the sulfur atom and the hydroxy group, which itself participates in the S-O-H···F bonds found in the crystal structure.…”
mentioning
confidence: 85%
“…The resulting theoretical vibrational modes represent the experimental spectra more closely than that of the free cation. [9] Supporting Information (see footnote on the first page of this article): Computational details.…”
Section: Equipment and Instrumentationmentioning
confidence: 99%
“…In addition, the vCCC model seems to yield values that appear to be too low for m (Figure 9). Recently, the protonation of fluorosulphonic acid in HF/SbF 5 has been reported, [61] which indicates that HSO 3 [58a] Due to their low autoprotolysis constants and their high dielectric constants, the ion activity coefficients are expected to be practically unity at their neutral point with pH 6.3 (HF) and 3.5 (HSO 3 F; cf. Debye-Hückel theory above).…”
mentioning
confidence: 99%